Relationship between text complexity, readers’ ability and tasks and readability. - Rasakumaran, A. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Readability, from a psycholinguistic perspective, is the intrinsic difficulty of texts to be understood. This paper presents the results of a study carried out to find out the relationship between linguistic complexity, readers’ ability and the comprehension tasks and the readability of a text. The research employed a quasi-experimental method where the complexity of texts was manipulated to construct two reading comprehension tests. The tests measured different aspects of reading comprehension, using an evaluation model based on psycholinguistic approach. The tests were administered to senior secondary students from three schools in the district of Jaffna, Sri Lanka. A total of 208 students participated in this study. The results revealed that not only the linguistic complexity of the text but also the readers’ ability and the nature of the comprehension tasks affected the readability of texts.
Keywords: Readability; Text Complexity; Readers’ Ability; Tasks